Students’ Understanding of Ambiguous Sentences in Websites - Dennis Dennis; Ienneke Indra Dewi (Bina Nusantara University, 2011)
Article intended to find out the most frequent ambiguity that could be found in the sentences and the intended meaning. Data were taken from Kaskus and Facebook web sites, and then tests were given to students who had learned syntax and semantics to know their ability in noticing ambiguous sentences. The results show that there are among 13 sentences or phrases, 12 of them are lexically ambiguous and 1 sentence is structurally ambiguous. From the result, it can be concluded that there are many people making an ambiguous sentence without realizing it.